Analytical and Computational Studies of Correlations of Hydrodynamic Fluctuations in Shear Flow (Communications in Computational Physics, 2018)
We study correlations of hydrodynamic fluctuations in shear flow analyticallyand also by dissipative particle dynamics (DPD) simulations. The hydrodynamicequations are linearized around the macroscopic velocity field and then solvedby a perturbation method in Fourier-transformed space. The autocorrelation functions(ACFs) from the analytical method are compared with results obtained from DPDsimulations under the same shear-flow conditions. Up to a moderate shear rate, variousACFs from the two approaches agree with each other well. At large shear rates,discrepancies between the two methods are observed, hence revealing strong additionalcoupling between different fluctuating variables, which is not considered in theanalytical approach. In addition, the results at low and moderate shear rates can serveas benchmarks for developing multiscale algorithms for coupling of heterogeneoussolvers, such as a hybrid simulation of molecular dynamics and fluctuating hydrodynamicssolver, where thermal fluctuations are indispensable.
Keywords: Hydrodynamic fluctuations; correlation functions; dissipative particle dynamics; shear flow.